Zgodovina raziskovanja tekočih kristalov - Južnič, Stanislav (Vakuumist, 2002)
The changes in the description of the liquid crystals was investigated that followed the research with physical methods in the beginning of the 20th century. The other sort of changes followed the use of the (thermotropic) liquid crystals as one of the most sophisticated technologies in the second part of the 20th century. Finally, the next stage of changes would be caused by the research of (lyotropic) liquid crystals in biochemistry, into which they are returning nowdays after more than a century of research in the solid state physics. A special concern was put on the research done in the Habsburg monarchy and in Ljubljana as a part of it. It is claimed that exceptionally quick acceptance of the early scientific research of the crystalography in Habsburg monarchy and in Carniola was connected with the mining industry in those areas. Some main researches leading to the discovery of the liquid crystals were performed in Habsburg monarchy. That research tradition was connected with the success of the contemporary research in Ljubljana of the phase transitions, especially with NMR, that influenced the modern description of liquid crystals.
Keywords: tekoči kristali; zgodovinski pregledi; crystallography; kristalografija